Design and Manufacture of Portable Coffee Roaster with LPG Heater System - Dedi Suryadi; Satryo Ramadhani; Agus Suandi; Nurul Iman Suparrdi; Novalio Daratha (Politeknik Negeri Lhokseumawe, 2023)
Bengkulu Province is one of Indonesia's top coffee producers. However, coffee processing is still done traditionally. Therefore, modern processing is required, particularly in the roasting process, which is vital in deciding the flavor of the coffee. This study aims to design, build, and test a low-energy coffee roaster with a capacity of 2 kg. The components of a coffee roaster are designed according to the demands and relevant standards, such as drum volume, drum material, shaft size, pulley size, belt, burner stove, and motor parameters. The coffee roaster is then tested by altering the distance between the fire holes to 10, 15, and 20 mm with a diameter of 3 mm, as well as varying the rotating speed of the drum to 60, 65, and 70 rpm and varying the coffee varieties, namely Robusta and Arabica. The testing of coffee roasting equipment with a capacity of 2 kg went smoothly. The results show that the ideal distance of the stove burner hole to attain 200 °C was discovered at a distance of 10 mm and a distance of the stove to the drum of 10 mm with a time of 17.24 minutes. For Robusta and Arabica coffee beans testing, the light roast should be roasted for 10 minutes. The medium roast requires 15 minutes of roasting time. And the dark roast requires a 20-minute roasting process. Furthermore, the rotating speed of the drum has little influence on the character of roasted coffee beans